Analysis of the Meaning of Punk in the Film Bomb x City (Semiotic Descriftive Study of the film Bomb x City) - Jordan Ronal; Sapta Sari; Anis Endang Sri Murwani (SENGKUNI Journal (Social Science and Humanities Studies), 2021)
This study aims to see what punk means in the movie Bomb X City. This study uses a qualitative method generate descriptive data. The grand theory in this study uses the semiotics of Roland Barthes which consists of denotation, connotation and myth. The results of this study proves that the meaning of punk in the movie Bomb X City is punk not a group of young people who are always in the environment. Their styles are tattoos, piercings, all black clothes and colored hair only as a form of expression of the young people themselves and according to the author it is owned in everyone including The Preps.